Impact of deforestation on water chemistry in the western Tatras and Beskid Śląski Range in the Polish Carpathians - Amanda Kosmowska; Mirosław Żelazny; Stanisław Małek; Tomasz Stańczyk (Acta Scientiarum Polonorum. Formatio Circumiectus)
The article describes the research into the impact of deforestation on the values of physicochemical traits and chemical composition of waters which drain the catchments covered with forest, and those that have been deforested, in the western part of Polish Carpathians. The research was carried out in independent catchments in the Skrzyczne massif in the Beski Śląski (Silesian Beskidy Range) in 2013–2014, and in the Kościeliska Valley in the Western Tatras in 2015–2016. During field studies, water samples were collected monthly in catchments with various degrees of deforestation, and the physicochemical characteristics of water were measured (pH, PEW, Tw). In the laboratory, the chemical composition of water, specifically the content of 14 ions (Ca2+, Mg2+, Na+, K+, NH4 +, Li+, HCO3–, SO42–, Cl–, NO2–, NO3–, PO43–, Br–, F–), was determined by means of ion chromatography (DIONEX 2000). The conducted research has shown the impact of deforestation on the value of physical and chemical traits and chemical composition of water. Deforestation of the slopes caused changes in the structure of the chemical composition of water, especially in the area of correlations between anions. In the Tatras, in the basins deforested as a result of windfall, a significant increase in the proportion of NO3 – (% mval ∙ dm–3) in the anionic element of the chemical composition of water was observed, and in the Beskid Śląski, in catchments deforested due to the tree stand decay associated with the imission of pollutants, a significant increase in SO4 2– (% mval ∙ dm–3) and a significant decrease in HCO3 – (% mval ∙ dm–3) in the anionic structure of the chemical composition of waters was observed. These examples document the extremely important role played by forests, which cover mountain slopes, in the hydrochemical functioning of the catchment. In the spatial aspect, there is an unusual phenomenon of hydrochemical mosaicism consisting in the occurrence of different relationships between anions, especially hydrogen carbonates, sulphates and nitrates.